Skills of the Forensic Accountants in Revealing Fraud in Public Sector: The Case of Indonesia - Sumartono Sumartono; Dekar Urumsah; Rizki Hamdani (Journal of Accounting and Investment, 2020)
Research aims: This paper aims primarily to investigate the effect of the skills of forensic accountants on the public sector in revealing fraud in Indonesia. Therefore, this research focuses on the investigation of forensic accountants in the public sector.Design/Methodology/Approach: This study employed a quantitative approach with a survey method. Questionnaires were distributed to the auditors possessing experiences to conduct investigative auditing in the Audit Board of the Republik of Indonesia (BPK RI). In total, 44 respondents returned the questionnaires, which can be considered suitable for a descriptive survey.Research findings: The results showed that the investigative skill and business valuation affected significantly and positively, and then business skill had significant and negative effects on the skills of forensic accountants in revealing fraud in the public sectors. On the other hand, financial accounting skills had no significant impact on the skills of forensic accountants in revealing fraud in the public sectors.Theoretical contribution/Originality: This paper highlights various important skills possessed by forensic accountants in the public sector in revealing fraud in Indonesia.Practitioner/Policy implication: This paper contributes as the basis of institutions’ concerns such as recruiting future forensic accountants in the public sectors, and training and upgrading related to the investigative skill, and business valuation which is compulsorily possessed by forensic accountants.Research limitation/Implication: This study focused on the public sectors, in this case, the Audit Board of the Republik of Indonesia representative of  Yogyakarta province, and on succinct respondents. Future studies should add more institutions and respondents involved in the analysis process to gain a complete representation of the skills of forensic accountants.